Empowering Nagari through diaspora: the collective capital of Minangkabau migrant organisations - Nelmawarni, Nelmawarni; Rasyidin, Warnis; Rahmi, Lailatur; Ulfatmi, Ulfatmi; Syauqi, Khilal (Universiti Teknologi MARA, Perak, 2025)
This article analyzes the role of Minangkabau diaspora organisations as collective actors in empowering nagari (indigenous villages) in West This article analyzes the role of Minangkabau diaspora organisations as collective actors in empowering nagari (indigenous villages) in West Sumatra. The deeply rooted merantau (outmigration) tradition in Minangkabau culture has fostered expansive social and cultural networks that have evolved into institutionalised diaspora organisations. Employing a qualitative case study approach, this research draws on in-depth interviews, participant observation, and document analysis of organisations such as IKSP, PKDP, and S3. Findings reveal that these organisations maintain strong institutional frameworks and efficiently manage collective capital, encompassing social, cultural, and economic resources. This capital is mobilised through participatory and transparent development programs rooted in musyawarah nagari (local deliberative councils), focusing on infrastructure, education, productive economy, and cultural preservation. The programs reflect not only community-driven development but are also deeply informed by Minangkabau customary values and Islamic principles. The study concludes that Minangkabau diaspora organisations serve as strategic transnational actors in local development. Their contributions extend beyond financial remittances to embody social piety and collective agency. The article offers a theoretical contribution to diaspora-led development discourse, highlighting the relevance of institutionalised gotong royong (mutual cooperation) within localised governance systems.